Female CFOs, leverage and the moderating role of board diversity and CEO power - Schopohl, Lisa; Urquhart, Andrew; Zhang, Hanxiong (Journal of Corporate Finance, 2021)
This paper investigates the extent to which female Chief Financial Officers (CFOs) affect corporate leverage. We examine female CFOs in UK firms and find that they significantly reduce the leverage of the firm; however, a female CFO's ability to influence corporate leverage is moderated by the senior decision-making environment in the firm. In particular, female CFOs are more effective in reducing leverage in firms with boards that are diverse with respect to gender, nationality and age, and in firms where the Chief Executive Officer (CEO) is not overly powerful. In addition, we find that externally appointed female CFOs reduce leverage more, in line with them having less allegiances to other top managers and greater scope to deviate from existing policies. Our work contributes to the literature by examining the conditions under which gender-specific risk-taking preferences lead to observable effects on corporate outcomes.